Da liberdade de expressão ao discurso de ódio: análise dos limites do direito fundamental à livre manifestação do pensamento na sociedade da informação - (:unkn) unknown (Universidade Federal do Pampa, 2026)
The research in question aims to investigate the limits of freedom of expression on digital platforms and its relationship with the phenomenon of hate speech in the information age. The research problem consists of questioning whether there are clear criteria capable of distinguishing manifestations protected by the fundamental right to free expression from those that constitute discriminatory and offensive speech against vulnerable groups. The main objective is to analyze whether there are objective criteria capable of separating freedom of expression from hate speech on digital networks. Specific objectives include analyzing the fundamental right to the free manifestation of thought in light of Contemporary Brazilian Constitutionalism, investigating fundamental rights in the informational society, and identifying the existence—or lack thereof—of legal parameters that can assist in this distinction. The methodology employed is the hypothetical-deductive method, including bibliographic research, doctrinal analysis, examination of jurisprudence, and the study of emblematic cases, also addressing debates related to Theme 837 of the Brazilian Federal Supreme Court. The research indicates that freedom of expression is an essential element of democracy, although it is not absolute, facing limitations when it conflicts with other fundamental rights, such as human dignity, equality, and the protection of honor. It is concluded that the definition of objective criteria to distinguish freedom of expression from hate speech represents one of the main challenges of contemporary constitutional law, requiring a constant and balanced consideration of fundamental rights in the digital environment.
From Freedom of Expression to Hate Speech: An Analysis of the Limits of the Fundamental Right to Freedom of Thought and Expression in the Information Society
Keywords: Direitos fundamentais; Discurso de ódio; Liberdade de expressão; Fundamental rights; Hate speech; Freedom of expression; CIENCIAS SOCIAIS APLICADAS